Escape from autologous neutralizing antibodies in acute/early subtype C HIV-1 infection requires multiple pathways. - Rong Rong; Bing Li; Rebecca M Lynch; Richard E Haaland; Megan K Murphy; Joseph Mulenga; Susan A Allen; Abraham Pinter; George M Shaw; Eric Hunter; James E Robinson; S Gnanakaran; et al. (PLoS Pathogens)
One aim for an HIV vaccine is to elicit neutralizing antibodies (Nab) that can limit replication of genetically diverse viruses and prevent establishment of a new infection. Thus, identifying the strengths and weaknesses of Nab during the early stages of natural infection could prove useful in achieving this goal. Here we demonstrate that viral escape readily occurred despite the development of high titer autologous Nab in two subjects with acute/early subtype C infection. To provide a detailed portrayal of the escape pathways, Nab resistant variants identified at multiple time points were used to create a series of envelope (Env) glycoprotein chimeras and mutants within the background of a corresponding newly transmitted Env. In one subject, Nab escape was driven predominantly by changes in the region of gp120 that extends from the beginning of the V3 domain to the end of the V5 domain (V3V5). However, Nab escape pathways in this subject oscillated and at times required cooperation between V1V2 and the gp41 ectodomain. In the second subject, escape was driven by changes in V1V2. This V1V2-dependent escape pathway was retained over time, and its utility was reflected in the virus's ability to escape from two distinct monoclonal antibodies (Mabs) derived from this same patient via introduction of a single potential N-linked glycosylation site in V2. Spatial representation of the sequence changes in gp120 suggested that selective pressure acted upon the same regions of Env in these two subjects, even though the Env domains that drove escape were different. Together the findings argue that a single mutational pathway is not sufficient to confer escape in early subtype C HIV-1 infection, and support a model in which multiple strategies, including potential glycan shifts, direct alteration of an epitope sequence, and cooperative Env domain conformational masking, are used to evade neutralization.